Hybrid Diesel Locomotive Control Method - 李小文 (机车电传动)
The control method of hybrid diesel locomotive based on diesel and battery and the composition of hybrid diesel locomotive electric drive system was introduced, and the locomotive states control, battery control, power matching, braking energy recovery were declared, corresponding control method of which was proposed.